1991
DOI: 10.1177/014107689108400913
|View full text |Cite
|
Sign up to set email alerts
|

Levels of Visual Impairment in a Day Centre for People with a Mental Handicap

Abstract: A prospective study screening for visual impairment in a day centre for people with a mental handicap showed that 30% required spectacles or registration as blind or partially-sighted and a further 20% had previously unknown pathology. Carers were not reliable in identifying visual problems in their charges, and routine screening should be encouraged. High Street optometrists should be able to measure visual acuity in the individuals in this sample excluding those cared for in special care units for whom scree… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

1993
1993
2018
2018

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 5 publications
1
13
0
Order By: Relevance
“…Haire and coworkers in 1991 reported that in a sample of 61 mentally handicapped patients where 19 patients had DS, 17 patients (28% of the total sample) had visual impairment with visual acuities of less than 20/60 11. Van Schrojenstein Lantman-de Valk et al in 1994 and 1997 assessed 243 DS individuals and reported a visual impairment prevalence of 36.2%–59.1% in the 30–59-year age group 12.…”
Section: Discussionmentioning
confidence: 99%
“…Haire and coworkers in 1991 reported that in a sample of 61 mentally handicapped patients where 19 patients had DS, 17 patients (28% of the total sample) had visual impairment with visual acuities of less than 20/60 11. Van Schrojenstein Lantman-de Valk et al in 1994 and 1997 assessed 243 DS individuals and reported a visual impairment prevalence of 36.2%–59.1% in the 30–59-year age group 12.…”
Section: Discussionmentioning
confidence: 99%
“…[52][53][54][55][56][57][58][59] In addition, people with ID may be less likely to report visual symptoms or to have regular ophthalmic care. 60 -62 The method of screening may need to be individualized for patients with communication and perception limitations.…”
Section: Given the High Rates Of Osteoporosis Documented Among Adultsmentioning
confidence: 99%
“…Individuals aged from 15 to > 65 years from a day centre in England were screened by an ophthalmologist and an optometrist in a study by Haire et al (1991). These authors measured visual acuity in 61 out of the 75 users with Snellen charts or Kay pictures.…”
Section: Previous Studiesmentioning
confidence: 99%